“Aunque al seco tronco lo sigan regando” – Reprises du muralisme chez les grupos (1968-1978) - Annabela Tournon (Nuevo mundo - Mundos Nuevos, 2014)
This paper seeks to understand the modalities of the recovery of muralism, both in theoretical and practical terms, by the « grupos » (collectives of artists, theorists and activists working in Mexico in the 1970s) through two case studies : a mural painting produced in the aftermath of the 68’ by the Grupo 65, and an exhibition of muralism in 1978. This two objects of analysis, subsuming artworks, discourses and events, allow to observe in their diversity the appropriations by the grupos of muralism, between popular uses and marxist rereadings, but also to bring new elements for the understanding of the event of 1968.